Modeling the Time‐Dependent Magnetic Fields That BepiColombo Will Use to Probe Down Into Mercury's Mantle. Issue 2 (14th January 2023) - Zomerdijk‐Russell, S.; Masters, A.; Korth, H.; Heyner, D.
Abstract: External solar wind variability causes motion of the magnetopause and changes of this boundary's current structure, and the resulting inductive processes, may be exploited to determine the interior structure of magnetized planets. In preparation for the arrival of the BepiColombo spacecraft at Mercury, we here assess solar wind ram pressure forcing in this planet's environment, through analysis of data acquired by the Helios spacecraft, and the impact on the magnetopause's inducing field. These measurements suggest that BepiColombo will see highly unpredictable solar wind conditions and that the inducing field generated in response to variable solar wind ram pressure is non‐uniform across the planet's surface. The inducing magnetic field spectrum, with frequencies in the range of ∼ 5.5 × 10 − 5 – 1.5 × 10 − 2 H z $\sim 5.5× {10}^{-5}--1.5× {10}^{-2}Hz$, suggests that the transfer functions derived from the two BepiColombo spacecraft could allow us to obtain a profile of conductivity through Mercury's crust and mantle. Plain Language Summary: In order to develop our understanding of the formation and evolution of Mercury, and hence, the mechanisms involved in the formation of our solar system, we need to precisely determine the interior composition of the terrestrial planet. Due to Mercury's magnetic field, that similar to Earth is produced in its liquid iron core, a layer of electric current shields the planet from the stream of charged particles ejected from the Sun, known as the solar wind. As Mercury is very close to the Sun, this current layer is strongly under the influence of the variable solar wind and the magnetic field of the Sun embedded in it. Here, we assess how changes in the solar wind impact this layer of current and how we could use this process as a natural metal detector to probe planet's interior when the BepiColombo mission arrives at Mercury in 2025. Key Points: Inductive processes due to forcing of Mercury's magnetosphere by solar wind can be used by BepiColombo to probe the planet's interior Variable solar wind seen by Helios results in a non‐uniform inducing field at Mercury's surface similar to that BepiColombo will see Frequencies in derived inducing field spectra could be used to obtain a conductivity profile through to Mercury's mantle with BepiColombo